Exploring the Effects of Meditation Techniques Used by Mindfulness-Based Programs on the Cognitive, Social-Emotional, and Academic Skills of Children: A Systematic Review - Filipe, Marisa G.; Magalhães, Sofia; Veloso, Andreia S.; Costa, Ana Filipa; Ribeiro, Lúcia; Araújo, Patrícia; Castro, São Luís; Limpo, Teresa (Frontiers in Psychology, 2021)
There is evidence for the positive impact of mindfulness in children. However, little is known about the techniques through which mindfulness practice results in differential out-comes. Therefore, this study intended to systematically review the available evidence about the efficacy of meditation techniques used by mindfulness-based programs on cognitive, socio-emotional, and academic skills of children from 6 to 12 years of age. The review was registered on the PROSPERO database, and the literature search was conducted according to PICO crite-ria and PRISMA guidelines. The EBSCO databases were searched, and 29 studies were eligi-ble: nine randomized controlled trials and 20 quasi-experimental studies. All the included ran-domized controlled trials were rated as having a high risk of bias. Overall, the evidence for mindfulness techniques improving cognitive and socio-emotional skills was reasonably strong. Specifically, for cognitive skills, results showed that all the interventions used ‘body-centered meditations’ and ‘mindful observations’. Regarding socio-emotional skills, although all the studies applied ‘body-centered meditations’ and ‘mindful observations’, ‘affect-centered medi-tations’ were also frequent. For academic skills, just one quasi-experimental trial found im-provements, thus making it difficult to draw conclusions. Further research is crucial to evaluate the unique effects of different meditation techniques on children's cognitive, social-emotional, and academic skills.